Associations of circulating proteins with lipoprotein profiles: proteomic analyses from the OmniHeart randomized trial and the Atherosclerosis Risk in Communities (ARIC) Study. - Kim, Hyunju.; Lichtenstein, Alice H; Ganz, Peter.; Miller, Edgar R; Coresh, Josef.; Appel, Lawrence J; Rebholz, Casey M (Tufts University. Tisch Library., 2023)
Keywords: Nutrition, Nutrition/Carbohydrate, Nutrition/Protein, Proteomics, Lipoproteins, Clinical trials, Feeding study, Macronutrients, Dietary patterns.; Springer Open.